Change in antimicrobial susceptibility of pathogens isolated from surgical site infections over the past decade in Japanese nation-wide surveillance study. Issue 7 (July 2021) - Ueda, Takashi; Takesue, Yoshio; Matsumoto, Tetsuya; Tateda, Kazuhiro; Kusachi, Shinya; Mikamo, Hiroshige; Sato, Junko; Hanaki, Hideaki; Mizuguchi, Toru; Morikane, Keita; Kobayashi, Minako; Harihara, Yasushi; et al.
Abstract: Inappropriate antimicrobial therapy for surgical site infections (SSIs) can lead to poor outcomes and an increased risk of antibiotic resistance. A nationwide survey was conducted in Japan from 2018 to 2019 to investigate the antimicrobial susceptibility of pathogens isolated from SSIs. The data were compared with those obtained in 2010 and 2014–2015 surveillance studies. Although the rate of detection of extended-spectrum β-lactamase producing strains of Escherichia coli was increased from 9.5% in 2010 to 23% in 2014–2015, the incidence decreased to 8.7% in 2018–2019. Although high susceptibility rates were detected to piperacillin/tazobactam (TAZ), the geometric mean MICs were substantially higher than to meropenem (2.67 vs 0.08 μg/mL). By contrast, relatively low geometric mean MICs (0.397 μg/mL) were demonstrated for ceftolozane/TAZ. Although the MRSA incidence rate decreased from 72% in the first surveillance to 53% in the second, no further decrease was detected in 2018–2019. For the Bacteroides fragilis group species, low levels of susceptibility were observed for moxifloxacin (65.3%), cefoxitin (65.3%), and clindamycin (CLDM) (38.9%). In particular, low susceptibility against cefoxitin was demonstrated in non-fragilis Bacteroides, especially B. thetaiotaomicron . By contrast, low susceptibility rates against CLDM were demonstrated in both B. fragilis and non-fragilis Bacteroides species, and a steady decrease in susceptibility throughout was observed (59.3% in 2010, 46.9% in 2014–2015, and 38.9% in 2018–2019). In conclusion, Japanese surveillance data revealed no significant lowering of antibiotic susceptibility over the past decade in organisms commonly associated from SSIs, with the exception of the B. fragilis group.